Sistem Informasi Monitoring Tugas Siswa di Madrasah Tsanawiyah BPI Baturompe untuk Optimalisasi Pengelolaan Data Akademik - Warnilah, Ai Ilah; Sutisna, Herlan; Pertiwi, Melisa Winda; Ratningsih, Ratningsih (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
MTs BPI Baturompe as an educational institution has a strategic role in producing a generation that excels academically and has noble character. However, the process of managing student assignments and academic data that is still done manually causes various obstacles, such as delays in collecting assignments, difficulty monitoring, and lack of data integration. To answer these challenges, this service activity aims to develop a Student Assignment Monitoring Information System to improve the efficiency, accuracy, and integration of academic data management. This system will include features for monitoring assignments, managing assignment data, and communicating between teachers and students regarding assignments. It is expected that the implementation of this system can facilitate access to information, support the teaching and learning process, and improve the overall quality of learning at MTs BPI Baturompe. This system is designed to facilitate task monitoring, data management, and communication between teachers and students. With this system, the academic process becomes more efficient, accurate, and integrated. Hopefully, the implementation of this system can strengthen the teaching and learning process, facilitate access to information, and improve the overall quality of education. This activity is expected to be a real contribution in supporting the digitalization of education in the school environment, especially at MTs BPI Baturompe